Anxiety level in pregnant women in the first year of COVID-19 pandemic - Tamburaci, Esra (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: The study was aimed to determine the effect of the ongoing infection on the anxiety level of pregnant women during the first year of the COVID-19 pandemic. Methods: In this study, a structured questionnaire and the Beck anxiety inventory were administered to pregnant women who volunteered to participate in the research among the ones who applied to the outpatient clinic for routine prenatal care from January 2021-March 2021. Results: The study featured 200 pregnant women with a mean age of 28.3±6.8 years and a range of 18-45 years. The patients were divided into four groups according to their Beck score as minimal (38.5%), mild (42%), moderate (15.5%), and severe (4%) levels of anxiety. Women with moderate and severe levels of anxiety were observed to have higher rates of fear of getting infected with COVID-19, fear of infecting the baby, fear of death due to COVID-19, fear of losing her relative due to COVID-19, fear of losing her baby due to COVID-19, and fear of quarantine (p<0.001). Factors that independently affected the level of anxiety in pregnant women were examined by multivariate linear regression analysis. It was found that increasing age (β=0.246; p<0.001), fear of getting infected with COVID-19 (β=0.375; p<0.001), fear of death due to COVID-19 (β=0.105; p=0.044) and fear of losing her baby due to COVID-19 (β=0.205; p<0.001) positively associated with anxiety levels. Conclusions: Because of the detrimental impact on both the mother and the infant, perinatal mental wellbeing is a major public health concern. Thus, aside from the follow-up of pregnant women by a multidisciplinary team of perinatology, neonatology, and intensive care specialists, it is essential to provide psychosocial support during the pandemic.